Extracellular vesicles produced by human-induced pluripotent stem cell-derived endothelial cells can prevent arterial stenosis in mice via autophagy regulation - He, Yecheng; Li, Quanfu; Feng, Feng; Gao, Rupan; Li, Huadong; Chu, Yuxin; Li, Shaobo; Wang, Yin; Mao, Ruoying; Ji, Zhongzhong; Hua, Yutao; Shen, Jun; et al. (Frontiers in Cardiovascular Medicine, 2022)
Intravascular transplantation of human-induced pluripotent stem cells (hiPSCs) demonstrated a significant therapeutic effect in the treatment of restenosis by the paracrine function of extracellular vesicles (EVs). However, the risk of tumorigenicity and poor cell survival limits its clinical applications. In this study, we for the first time applied a highly efficient and robust three-dimensional (3D) protocol for hiPSC differentiation into endothelial cells (ECs) with subsequent isolation of EVs from the derived hiPSC-EC (ECs differentiated from hiPSCs), and validated their therapeutic effect in intimal hyperplasia (IH) models. We found that intravenously (iv) injected EVs could accumulate on the carotid artery endothelium and significantly alleviate the intimal thickening induced by the carotid artery ligation. To elucidate the mechanism of this endothelial protection, we performed miRNA expression profiling and found out that among the most conserved endothelial miRNAs, miR-126 was the most abundant in hiPSC-EC-produced EVs (hiPSC-EC-EV). MiR-126 depletion from hiPSC-EC-EV can hinder its protective effect on human umbilical vein endothelial cells (HUVECs) in an inflammatory process. A variety of functional in vitro studies revealed that miR-126 was able to prevent endothelial apoptosis after inflammatory stimulation, as well as promote EC migration and tube formation through autophagy upregulation. The latter was supported by in vivo studies demonstrating that treatment with hiPSC-EC-EV can upregulate autophagy in mouse carotid artery ECs, thereby preventing IH and modulating vascular homeostasis via remodeling of the vascular intima. Our findings suggest a regulatory mechanism for the therapeutic effect on arterial restenosis by autophagy regulation, and provide a potential strategy for clinical treatment of the disease.